Liver Cirrhosis of the Viral Etiology in Children - F. I. Inoyatova; G Z. Inogamova (Детские инфекции (Москва))
The structure of liver cirrhosis (LC) in children of Uzbekistan was studied. 135 children with viral etiology of liver cirrhosis at the age of 7—15 years of life were examined. It was established that in the structure of viral liver cirrhosis in children, mixed etiology prevails (77.1%) with a predominance of HDV infection (B + C + D — 35.6% and B + D — 23.7%). Mixed infection is considered as a predictor of disease progression, especially in cases of overlap of HDV infection, which was also expressed by the frequent identification of the decompensated stage of the liver cirrhosis C-class of Child-Pugh and complications. Levels of N-terminal propeptides and C-terminal telopeptides of type I collagen in children with liver cirrhosis can serve as markers of compensation and progression of the disease.